The Effects of ACT Treatment and TS Prophylaxis on Plasmodium falciparum Gametocytemia in a Cohort of Young Ugandan Children - Kakuru, Abel (The American Society of Tropical Medicine and Hygiene, 2013)
Artemisinin-based combination therapies (ACTs) and trimethoprim-sulfamethoxazole (TS) prophylaxis are important tools for malaria control, but there are concerns about their effect on gametocytes, the stage of the parasite responsible for transmission. We conducted a longitudinal clinical trial in a cohort of HIV-infected and uninfected children living in an area of high malaria transmission intensity in Uganda. Study participants were randomized to artemether-lumefantrine (AL) or dihydroartemisinin-piperaquine (DP) for all treatments of uncomplicated malaria (N = 4,380) as well as TS prophylaxis for different durations. The risks of gametocytemia detected by microscopy in the 28 days after antimalarial therapy were compared using multivariate analyses. The risk of gametocyte detection was significantly higher in patients treated with DP compared with AL (adjusted relative risk = 1.85, P < 0.001) and among children prescribed TS prophylaxis (adjusted relative risk = 1.76, P < 0.001). The risk of gametocytemia and its potential for increasing transmission should be considered when evaluating different ACTs and TS prophylaxis for malaria control.